EFEKTIVITAS PROGRAM PENGAJARAN TERHADAP MOTIVASI BELAJAR SISWA MELALUI PROGRAM KKN DI SDN 03 WAGIR - Ratih Soko Aji Jagat; Lutfia Rosidah; Anisa Nur Rahma; Irvan Iswandi; Dede Indra Setiabudi (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2022)
The purpose of writing on the study was to know and analyze the carried out of the teaching activities performed by the student keat in the wagir village ward. The method used is a qualitative descriptive study method using a two-form teaching technique - the teaching at school and outside the school guidance of the home-study system. As for research obtained on school teaching activities during 3 meetings, student motivation in learning increases. While in home study programs, the evaluations made at each meeting are obtained that an increased level of student motivation is generated from a change of behavior in the realm of affective senses. As for the increase in attendance attendance at any meeting of the home learning program also indicates a student's enthusiasm in following the learning process.